2021
DOI: 10.21203/rs.3.rs-953343/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Immune-Related lncRNA Model for Predicting Prognosis, Immune Landscape and Chemotherapeutic Response in Bladder Cancer

Abstract: Objective: Long noncoding RNAs (lncRNAs) participate in cancer immunity. Herein, we characterized the clinical significance of immune-related lncRNA model and its associations with immune infiltrations and chemosensitivity in bladder cancer.Methods: Transcriptome data of bladder cancer specimens were employed from The Cancer Genome Atlas. Dysregulated immune-related lncRNAs were screened via Pearson correlation and differential expression analyses, followed by recognition of lncRNA pairs. Then, a LASSO regress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Thus, a diversified analysis combined with de novo tumor markers would be more conducive to accurate prediction. In recent years, numerous studies have found that lncRNAs are closely related to the prognosis of patients with urological tumors [11][12][13][14]. Therefore, an in-depth study of lncRNAs would be beneficial in identifying de novo markers associated with the prognosis of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a diversified analysis combined with de novo tumor markers would be more conducive to accurate prediction. In recent years, numerous studies have found that lncRNAs are closely related to the prognosis of patients with urological tumors [11][12][13][14]. Therefore, an in-depth study of lncRNAs would be beneficial in identifying de novo markers associated with the prognosis of BC.…”
Section: Discussionmentioning
confidence: 99%